2010
DOI: 10.1371/journal.pone.0015823
|View full text |Cite
|
Sign up to set email alerts
|

1, 9-Pyrazoloanthrones Downregulate HIF-1α and Sensitize Cancer Cells to Cetuximab-Mediated Anti-EGFR Therapy

Abstract: Cetuximab, a monoclonal antibody that blocks the epidermal growth factor receptor (EGFR), is currently approved for the treatment of several types of solid tumors. We previously showed that cetuximab can inhibit hypoxia-inducible factor-1 alpha (HIF-1α) protein synthesis by inhibiting the activation of EGFR downstream signaling pathways including Erk, Akt, and mTOR. 1, 9-pyrazoloanthrone (1, 9 PA) is an anthrapyrazolone compound best known as SP600125 that specifically inhibits c-jun N-terminal kinase (JNK). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…To determine whether 1-methyl-1, 9 PA could mimic the effect of HIF-1α silencing on sensitizing cisplatin-resistant ovarian cancer cells to cisplatin, we first confirmed that 1-methyl-1, 9 PA could downregulate HIF-1α in A2780, A2780/CP, PEO1, and PEO4 cells, as we previously reported it did in many other cancer cell lines [31]. We then determined whether 1-methyl-1, 9 PA could improve the response of the cells to cisplatin treatment in an HIF-1α downregulation-dependent manner.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…To determine whether 1-methyl-1, 9 PA could mimic the effect of HIF-1α silencing on sensitizing cisplatin-resistant ovarian cancer cells to cisplatin, we first confirmed that 1-methyl-1, 9 PA could downregulate HIF-1α in A2780, A2780/CP, PEO1, and PEO4 cells, as we previously reported it did in many other cancer cell lines [31]. We then determined whether 1-methyl-1, 9 PA could improve the response of the cells to cisplatin treatment in an HIF-1α downregulation-dependent manner.…”
Section: Resultssupporting
confidence: 58%
“…We previously reported that a derivative of 1, 9-pyrazoloanthrone (1, 9 PA), 1-methyl-1, 9 PA, can induce strong downregulation of HIF-1α in multiple types of cancer cells by promoting HIF-1α protein degradation via the ubiquitination pathway [31]. To determine whether 1-methyl-1, 9 PA could mimic the effect of HIF-1α silencing on sensitizing cisplatin-resistant ovarian cancer cells to cisplatin, we first confirmed that 1-methyl-1, 9 PA could downregulate HIF-1α in A2780, A2780/CP, PEO1, and PEO4 cells, as we previously reported it did in many other cancer cell lines [31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For measurement of cell proliferation, cells were incubated in a 24-well plate with 1 mg/ml 3-(4,5-dimeth-ylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) for 2 h at the end of the desired treatments in cell culture [4749]. Cells were then lysed with a lysis buffer (500 µl/well) containing 20% SDS in dimethyl formamide/H 2 O (1:1, v/v; pH 4.7) at 37°C for at least 6 h. Optical density of the cell lysates was measured at an absorbance wavelength of 570 nm.…”
Section: Methodsmentioning
confidence: 99%